Architecture of the Interface between the Perovskite and Hole‐Transport Layers in Perovskite Solar Cells. Issue 18 (1st September 2016) - Moriya, Masahiro; Hirotani, Daisuke; Ohta, Tsuyoshi; Ogomi, Yuhei; Shen, Qing; Ripolles, Teresa S.; Yoshino, Kenji; Toyoda, Taro; Minemoto, Takashi; Hayase, Shuzi
Abstract: The interface between the perovskite (PVK, CH3 NH3 PbI3 ) and hole‐transport layers in perovskite solar cells is discussed. The device architecture studied is as follows: F‐doped tin oxide (FTO)‐coated glass/compact TiO2 /mesoporous TiO2 /PVK/2, 2′, 7, 7′‐tetrakis‐( N, N ‐di‐4‐methoxyphenylamino)‐9, 9′‐spirobifluorene (Spiro‐MeOTAD)/Au. After a thin layer of 4, 4, 4‐trifluorobutylammonium iodide (TFBA) was inserted at the interface between PVK and Spiro‐MeOTAD, the photovoltaic efficiency increased from 11.6–14.5 % to 15.1–17.6 %. TFBA (10 ppm) was added in the PVK solution before coating. Owing to the low surface tension of TFBA, TFBA rose to the surface of the PVK layer spontaneously during spin‐coating to make a thin organic layer. The PVK grain boundaries also seemed to be passivated with the addition of TFBA. However, large differences in Urbach energies and valence band energy level were not observed for the PVK layer with and without the addition of TFBA. The charge recombination time constant between the PVK and the Spiro‐MeOTAD became slower (from 8.4 to 280 μsec) after 10 ppm of TFBA was added in the PVK. The experimental results using TFBA conclude that insertion of a very thin layer at the interface between PVK and Spiro‐MeOTAD is effective for suppressing charge recombination and increasing photovoltaic performances. Abstract : Smooth it over : The perovskite (PVK) grain boundaries were passivated with fluoro‐ and amine‐substituted surfactant molecules, serving to provide low surface energy and as anchoring groups, respectively, such as 4, 4, 4‐trifluorobutylamine hydroiodide (TFBA). Charge recombination at the interface between passivated PVK and the hole‐transport layer was suppressed and the power conversion efficiency of a device fabricated with this passivated PVK layer was enhanced.